ANALISIS PENGARUH CITRA MEREK, KUALITAS MEREK TERHADAP MINAT BELI MIXUE PADA MASYARAKAT KOTA CIREBON - Ade Ambarita; Sahara; Tedi Kustandi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of brand image and brand quality on the purchase interest of Mixue consumers in Cirebon City. In an increasingly competitive business world, understanding consumer behavior is crucial, especially in building purchase interest. Mixue, a Chinese brand of drinks and ice cream, has successfully attracted consumer attention in Indonesia, including in Cirebon City. This research uses a quantitative approach with a descriptive design, involving 98 respondents. The results show that Mixue's brand image has a significant impact on purchase interest, followed by brand quality, which also has a positive influence. Overall, the combination of a strong brand image and consistent product quality makes Mixue superior compared to its competitors in the ice cream and beverage market in Cirebon City.